On Possible Mechanism of Damage in Frozen-Thawed Biological Objects Due to Pressure Plastic Relaxation in Closed Liquid Phase Inclusions - Osetsky, A. I.; Kirilyuk, A. L.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2007)
One of the possible causes of damages of cell suspensions, tissues and organs under sub-eutectic temperatures has been considered. Kinetics of the processes, proceeding during cooling and heating of aqueous solutions of cryoprotective agents was studied with tensodilatometric method and the one of thermoplastic deformation. There have been established temperature intervals for aqueous solutions of dimethyl sulfoxide, glycerol and polyethylene oxide with molecular weight of 1500 where the formation of ice single crystals in closed inclusions is possible, that may be the cause of significant mechanical impairments during cryopreservation of biological objects. These damages are quite actively realized under low concentrations of cryoprotectants (to 10%). Mechanical damage of biological objects during cryopreservation which is likely associated to plastic relaxation of pressures in closed liquid inclusions were exemplified with cryopreservation of Saccaromyces cerevisiae cells.